Ortnogonal-to-unitary ensemble crossover in the electronic specific heat of metal namoclusters - Mukhin, S.I.; Kurapova, O.V.; Moiseev, I.I.; Vargaftik, M.N.; Volokitin, Y.E.; Mettes, F.L.; Jongh, L.J. (Физика низких температур, 2001)
We present a theoretical and experimental study on the influence of a magnetic